¿Es eficiente el actual sistema procesal penal de Irán? - Mehdi Fazli; Jalaleddin Ghiasi; Mohammad Khalil Salehi (Ius Humani. Jornal do direito, 2018)
This paper is a study about the efficiency of the criminal system designed in the new Criminal Procedure Code of Iran, that came into effect on June 22, 2015. Notwithstanding the notable legislator’s efforts, infrastructural and structural reforms have not been carried out. Accordingly, it is not expected to be as efficient as the previous laws due to the lack of fundamental reforms; reforms caused the improvement in “low-level efficiency” (saving resources in the economic sense) rather than in the “high-level” one (saving resources plus developing more justice). The analysis of the efficiency of the Code and proposal of fundamental reforms for having a high-level efficient Criminal Law in Iran are the main objectives of this paper. After an introduction (Chapters I and II), we made a historical approach of the Iranian system in this matter (Chapter III). Then, we analyze three types of efficiency (Chapter IV), attending to some infrastructural elements, some structural factors and other procedural aspects. At last, we synthetize four conclusions (Chapter V). Main conclusion is that efficiency in the system of criminal procedure would be only on low-level.